A targeted tiled amplicon sequencing approach for clade and subclade level differentiation of monkeypox virus from wastewater - Mathew Fisher; Jennifer Ali; Shayna Giesbrecht; Raveena Roopra; Veronica Carroll; Amber Papineau; Cody Buchanan; Nicholas Duan; Chrystal Landgraff (Scientific Reports)
Abstract Wastewater-based surveillance (WBS) has modernized in recent years and emerged as an important tool for the monitoring of viral pathogens, including monkeypox virus (MPXV). Here we describe a novel targeted amplicon sequencing method developed for clade and subclade characterization of MPXV from municipal wastewater. This new method addresses the limitations of PCR-based methods and the challenges of sequencing a pathogen displaying low viral load in municipal wastewater samples. A tiled amplicon scheme composed of 11 primer pairs targeting a 4.2 kb portion of the inverted terminal repeat (ITR) region of the MPXV genome was designed and tested. In silico analysis demonstrated high accuracy for clade and subclade calls using the full target region, with specific amplicons also exhibiting strong performance individually. An MPXV consensus sequence representing the entire target region was successfully sequenced from a wastewater sample and differentiated from positive controls by a distinct deletion within a short homopolymeric region. Notably, clade-informing data was also achieved from partial sequences recovered from lower abundance samples. This study presents a new sequencing method targeting MPXV with enhanced genomic resolution compared to existing PCR-based approaches, providing critical genomic-level information informing MPXV surveillance and public health interventions.